Exploiting high-resolution data to investigate the characteristics of water consumption at the end-use level: A Dutch case study - Mazzoni, Filippo; Alvisi, Stefano; Franchini, Marco; Blokker, Mirjam (Water resources and industry, 2023)
In the water industry, an accurate estimation of end-use water consumption is helpful for the implementation of efficient water systems and water-saving technologies. This study aimed to explore the characteristics of water consumption at nine households north of Amsterdam (the Netherlands), subjected to water consumption monitoring at high temporal resolution (i.e. 1 s). Overall, 36,297 water-use events monitored over about 447 days were automatically segmented into 44,115 individual events by means of a new rule-based filtering algorithm, and then labelled by expert analysts. A multi-stage analysis was then conducted in order to evaluate daily per capita end-use water consumption, daily end-use profiles, average end-use parameter average, and their statistical distributions. The results achieved provide insight into the features of end-use consumption, confirming that the largest components are typically related to showers/bathtubs, toilets, and washing machines, whereas different end-use parameter distributions can emerge. •High-resolution water consumption data were collected in nine Dutch households.•A novel automated methodology for water use event segmentation was applied.•The resulting 44,000 indoor water use events were manually clustered and labelled.•The study provides insight into the features of end-use water consumption.